A comparative analysis of the heterotrimeric G-protein G[alpha], G[beta] and G[gamma] subunits in the wheat pathogen Stagonospora nodorum - Gummer, J.; Trengove, R.; Oliver, Richard; Solomon, P. (BioMed Central Ltd., 2012)
Background: It has been well established that the Gα subunit of the heterotrimeric G-protein in the wheat pathogen Stagonospora nodorum is required for a variety of phenotypes including pathogenicity, melanisation and asexual differentiation. The roles though of the Gγ and Gβ subunits though were unclear. The objective of this study was to identify and understand the role of these subunits and assess their requirement for pathogenicity and development. Results: G-protein Gγ and Gβ subunits, named Gga1 and Gba1 respectively, were identified in the Stagonospora nodorum genome by comparative analysis with known fungal orthologues. A reverse genetics technique was used to study the role of these and revealed that the mutant strains displayed altered in vitro growth including a differential response to a variety of exogenous carbon sources. Pathogenicity assays showed that Stagonospora nodorum strains lacking Gba1 were essentially non-pathogenic whilst Gga1-impaired strains displayed significantly slower growth in planta. Subsequent sporulation assays showed that like the previously described Gα subunit mutants, both Gba1 and Gga1 were required for asexual sporulation with neither mutant strain being able to differentiate either pycnidia nor pycnidiospores under normal growth conditions. Continued incubation at 4°C was found to complement the mutation in each of the G-protein subunits with nearly wild-type levels of pycnidia recovered. Conclusion: This study provides further evidence on the significance of cAMP-dependent signal transduction for many aspects of fungal development and pathogenicity. The observation that cold temperatures can complement the G-protein sporulation defect now provides an ideal tool by which asexual differentiation can now be dissected.